Department of health COVID-19 infographics safety reminder: a semiotic analysis (Conference on English Language Teaching, 2023)
This study focuses on analyzing the semiotics of infographics used in healthcommunication, particularly in the context of COVID-19 control and prevention issuedby the Department of Health (DOH) in the Philippines. The objective is to identify,categorize, and interpret the visual signs employed in these infographics, consideringtheir denotative and connotative meanings. The study follows qualitative andinterpretative context analysis methods, using Charles Sanders Peirce's semiotic theoryas the framework. The researchers will carefully examine the visual content, includingobjects, people, colors, and shapes. Ethical considerations such as credibility,trustworthiness, transferability, confirmability, and dependability will be addressed. Theresearch corpus consists of five infographics issued by the DOH, each targeting differentaudiences and covering various aspects of COVID-19. The findings reveal a range ofvisual signs, including representations of respiratory symptoms, hand hygiene practices,medical professionals, news updates, and communication methods. Wearing face masks,seeking medical advice, and following proper etiquette is emphasized. The colorschemes and symbols effectively convey urgency, caution, and guidance. Visual signs inthe infographics play a crucial role in raising awareness and promoting public healthmeasures during the COVID-19 pandemic which contribute to a comprehensiveunderstanding of the messages conveyed through visual communication strategies.